The Effects of Drama Activity Utilizing Story-Telling on Vocal Vibration and Voice Energy of Pre-Kindergarten Teachers - Jai Kim, Hyoung; Hyun Kim, Bong; Sook Kim, Hyung (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of this study was to investigate the effects of drama activity utilizing story-telling on the vocal vibration and the voice energy of pre-kindergarten teachers. Methods/Statistical analysis: For the study, five pre-kindergarten teachers enrolled in the 4-year early childhood education department of the university in Yeongdong-gun in Korea were collected through the same space and recording device. We collected and analyzed their voice by using the praat voice analysis program that uses the pitch to measure the vocal vibration and the intensity to measure the voice energy. Findings: After this drama activity utilizing story-telling, the pitch and strength measurements of the pre-kindergarten were significantly higher than those before that activity. Improvements/Applications: It is suggested that this drama activity utilizing story-telling induces the interest and fun of the pre-kindergarten. Â